2018
DOI: 10.1007/s11205-018-1945-9
|View full text |Cite
|
Sign up to set email alerts
|

Which Aspects of Elderly Living Conditions are Important to Predict Mortality? The Complex Role of Family Ties at Home and in Institutions

Abstract: Besides health and socio-economic status, the social relationships maintained during elderly play an important role in shaping the living conditions at older ages. In this part of life, the family represents the major framework in which interpersonal relationships are experienced. With population ageing, the family increasingly ensures elderly care, especially where targeted public policies are lacking, and its protective effect on survival is foreseen. In this paper we investigate the complex role of family i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 111 publications
0
6
0
Order By: Relevance
“…Survival at adult and later ages is positively influenced by the quantity and the quality of both social relationships and support (Holt-Lunstad et al 2010 ; Shor et al 2013 ). Among the extended social net, family members, particularly partners and children, play a crucial role in this association (Giudici et al 2019 ; Modig et al 2017 ). Differential mortality by marital status has largely been investigated and has shown the benefits of being married.…”
Section: Introductionmentioning
confidence: 99%
“…Survival at adult and later ages is positively influenced by the quantity and the quality of both social relationships and support (Holt-Lunstad et al 2010 ; Shor et al 2013 ). Among the extended social net, family members, particularly partners and children, play a crucial role in this association (Giudici et al 2019 ; Modig et al 2017 ). Differential mortality by marital status has largely been investigated and has shown the benefits of being married.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on elderly living arrangements found that they increase health practice and behaviour changes daily in living activities (Wei et al, 2022). Similarly, as Ethisan et al (2017) and Giudici et al (2019) demonstrated, the elderly tend to seek the most appropriate living conditions, and in turn, exhibit behaviour in ways that show an increase in elderly health outcomes.…”
Section: Discussionmentioning
confidence: 92%
“…This finding is consistent with Simpson et al (2022), who found a connection between the elderly and community health based on strong ties, access to healthcare, and health communication. Giudici, Polettini, de Rose, and Brouard (2019) noted that strong network ties are necessary for accessing health information and living arrangements. This result is consistent with previous studies (Turnera et al, 2019; Whittaker & Gillespie, 2013), and our study demonstrated that strong network ties are more likely to enhance elderly health behaviours.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is relatively limited research on the specific issue of the role of the institutionalization on potential excess mortality. Based on longitudinal French data on people aged 60 and more, Giudici et al (2019) have estimated that people living in institutions live on average 10 years less that those living in private households. However, they did not take into account the potential issue of endogeneity, as people in nursing home differ from people staying at home.…”
Section: Literature Reviewmentioning
confidence: 99%